Effects of an experimental short-time high-intensity warm-up on explosive muscle strength performance in soccer players: A pilot study - Patti, Antonino; Giustino, Valerio; Hirose, Norikazu; Messina, Giuseppe; Cataldi, Stefania; Grigoli, Giuseppe; Marchese, Alida; Mulè, Giuseppe; Drid, Patrik; Palma, Antonio; Bianco, Antonino (Frontiers in Physiology, 2022)
Objective: This study aimed to evaluate the effects of an experimental short-time warm-up consisting of a small number of intermittent high-intensity sprints on explosive muscle strength performance in soccer players, and to identify recovery times after performing the sprints. Furthermore, we evaluated the reliability of a smartphone app in jumping performance. Methods: Twenty male soccer players were given the following tests: a) Counter Movement Jump (CMJ) test with Microgate system; b) Counter Movement Jump (CMJ) test with MyJump smartphone app; c) handgrip strength test. The experimental short-time high-intensity warm-up was carried out one week after tests administration. The warm-up consisted of 3 maximum sprints over 60 meters with 120 seconds of recovery between sprints. Then, the tests were administered again: the vertical jump height (VJH) performances (5 trials) were measured 90 seconds after the last sprint; the handgrip strength performances (3 trials) were measured 120 seconds after the last vertical jump test. Results: The maximum VJH was found in the third trial of the CMJ test, 330 seconds after the last sprint (p<0.01), the result closest to the baseline. The lowest VJH was found in the first trial of the CMJ test, 90 seconds after the last sprint (p<0.05). Pearson’s analysis between CMJ test with Microgate system and CMJ test with MyJump showed a strong correlation (R=0.96). Lin's concordance correlation coefficient showed a substantial concordance (ρc=0.959) between measures. Conclusion: This experimental short-time warm-up of high-intensity intermittent sprints appears to be a simple, quick, and efficient activity to accelerate soccer players’ optimal performance.